(NmETOD NEPRIWODIMYH TENZORNYH OPERATOROW W TEORII SPEKTROW MOLEKUL (B/s - (NvILINSKIJ(B, (NbORIS iGOREWI^s; (NpEREWALOW(B, (NwALERIJ iNNOKENTXEWI^s; (Nt@TEREW(B, (NwLADIMIR gRIGORXEWI^s; (NmAKU[KIN(B, (N`RIJ sEMENOWI^s; (NiN(B-(NT OPTIKI ATMOSFERY so an sssrs ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 221-231 (239 (NNAZW(B.)s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (NiN(B-(NT OPTIKI ATMOSFERYs
Keywords: (NpRIMENENIE W SPEKTROSKOPIIs; (NtENZORNOE IS^ISLENIEs